Discovery of novel secretome CAZymes from Penicillium sclerotigenum by bioinformatics and explorative proteomics analyses during sweet potato pectin digestion - Barrett, Kristian; Zhao, Hai; Hao, Pengfei; Bacic, Antony; Lange, Lene; Holck, Jesper; Meyer, Anne S. (Frontiers in Bioengineering and Biotechnology, 2022)
Novel selective enzymatic refining of sweet potato processing residues requires judicious enzyme selection and enzyme discovery. We prepared a pectinaceous cell wall polysaccharide fraction from sweet potato using mild chemical treatment to preserve the natural linkages and substitutions. Polysaccharide composition and linkage analysis data confirmed the fraction to be a rhamnogalacturonan I-rich fraction with high content of arabinogalactan Type I. We hypothesized that the tuber post-harvest pathogenic fungus Penicillium sclerotigenum would harbor novel enzymes targeting selective sweet potato pectin modification. As part of the study, we report the first genome sequence of P. sclerotigenum. We incubated the sweet potato pectinaceous fraction with P. sclerotigenum. Using proteomics accompanied by CUPP-bioinformatics analysis, we observed induced expression of 23 pectin-associated degradative enzymes. We also identified six abundantly secreted, induced proteins that do not correspond to known CAZymes, but which we suggest as novel enzymes involved in pectin degradation. For validation, the predicted CUPP grouping of putative CAZymes and the exo-proteome data obtained for P. sclerotigenum during growth on sweet potato pectin were compared with proteomics and transcriptomics data reported previously for pectin-associated CAZymes from Aspergillus niger strain NRRL3. The data infer that P. sclerotigenum has capacity to express several novel enzymes that may provide novel opportunities for sweet potato pectin modification and valorization of sweet potato starch processing residues. In addition, the methodological approach employed represents an integrative systematic strategy for enzyme discovery.